বাংলাদেশের গ্রাম : অতীত ও ভবিষ্যৎ - ইসলাম, নজরুল, ১৯৫৭-
Articles on the socio-economic condition of villages of Bangladesh; includes some articles on the social condition and structure of Indian villages.